Influence of particle size on ecotoxicity of low-density polyethylene microplastics, with and without adsorbed benzo-a-pyrene, in Clam Scrobicularia plana - Rodrigues, Ana Rita (2022)
This study investigated the ecotoxicological effects of differently sized (4–6 µm and 20–25 µm) low-density polyethylene (LDPE) microplastics (MPs), with and without adsorbed benzo-a-pyrene (BaP), in clam Scrobicularia plana. Biomarkers of oxidative stress (superoxide dismutase—SOD; catalase—CAT), biotransformation (glutathione-S-transferases—GST), oxidative damage (lipid peroxidation—LPO) and neurotoxicity (acetylcholinesterase—AChE) were analysed in gills and digestive glands at different time intervals for a total of 14 days of exposure. In order to have a better impact perspective of these contaminants, an integrated biomarker response index (IBR) and Health Index were applied. Biomarker alterations are apparently more related to smaller sized (4–6 µm) MPs in gills and to virgin LDPE MPs in the digestive gland according to IBR results, while the digestive gland was more affected by these MPs according to the health index.